Laboratory science with space data accessing and using space-experiment data - Beysens, Daniel; SpringerLink (Online service). (Berlin New York Springer, 2011)
For decades experiments conducted on space stations like MIR and the ISS have been gathering data in many fields of research in the natural sciences, medicine and engineering. The European Union-sponsored ULISSE project focused on exploring the wealth of unique experimental data provided by revealing raw and metadata from these studies via an Internet Portal. This book complements the portal. It serves as a handbook of space experiments and describes the various types of experimental infrastructure areas of research in the life and physical sciences and technology space missions that hosted scientific experiments the types and structures of the data produced and how one can access the data through ULISSE for further research. The book provides an overview of the wealth of space experiment data that can be used for additional research and will inspire academics (e.g. those looking for topics for their PhD thesis) and research departments in companies for their continued development.
1 Introduction -- 2 Space and Ground-Based Infrastructures -- 2.1 Characteristics of the Space Environment -- 2.2 Space Infrastructure -- 2.3 Non-orbital weightless research platforms -- 2.4 Ground-based facilities and space simulators -- 3 Areas of research -- 3.1 Physical sciences -- 3.2 Life sciences -- 4 ULISSE access to data -- 4.1 Data description -- 4.2 Identification of information: the ULISSE knowledge base -- 4.3 ULISSE: data access services.
Electronic reproduction.
Keywords: Space sciences; Electronic books